I find it difficult to construct the conditional probability $P(X_i = x_i\mid X_i + X_j = t)$. It's supposed to be ~BIN(t,$\frac{p_i}{pi+pj})$

I first use the definition of conditional probability.

$$P(X_i \mid X_i + X_j)= \frac{P(X_i=x_i \cap X_i + X_j=t)}{P(X_i + X_j=t)}$$

Now, for the numerator, I use the multinomial distribution, which gives

$$ \frac{n!}{x_i!(x_i+x_j)! (n-x_i-x_i-x_j)!} p_i^{x_i} (p_i+p_j)^{x_i+x_j} (1-p_i-p_i-p_j)^{n-x_i-x_i-x_j}$$

For the denominator, I write

$$ \frac{n!}{(x_i+x_j)! (n-x_i-x_j)!} (p_i+p_j)^{x_i+x_j} (1-p_i-p_j)^{n-x_i-x_j}$$

Combining them doesn't really cancel enugh things out. THis seems too complicated. Did I make a mistake somewhere?


Your mistake was to assume that $(X_i,X_i+X_j,\sum_{k\notin\{i,j\}} X_k)$ has a multinomial distribution. It is possible to combine components of a multinomial distribution to get another multinomial distribution, but for this to work we must use each component exactly once (i.e., we can't include $X_i$ as a term in both components).

$(X_1,X_2,\dots,X_n)$ are assumed to have a multinomial distribution with parameters $(p_1,p_2,\dots,p_n)$. It follows that for distinct $i,j$, $(X_i, X_j, \sum_{k\notin\{i,j\}}X_k)$ has a multinomial distribution with parameters $(p_i,p_j,\sum_{k\notin\{i,j\}} p_k)=(p_i,p_j,1-p_i-p_j)$. So we may calculate, \begin{align*} P(X_i=x_i \cap X_i+X_j=t) &= P(X_i=x_i \cap X_j=t-x_i \cap \sum_{k\notin\{i,j\}}X_k=n-t) \\ &= \frac{n!}{x_i!(t-x_i)!(n-t)!}p_i^{x_i}p_j^{t-x_i}\left(1-p_i-p_j\right)^{n-t} \end{align*} On the other hand, $X_i+X_j$ has a binomial distribution with parameters $n$ and $p_i+p_j$, so $$P(X_i+X_j=t) = \frac{n!}{t!(n-t)!}(p_i+p_j)^t(1-p_i-p_j)^{n-t}$$ Therefore, \begin{align*} P(X_i=x_i \mid X_i+X_j=t) &= \frac{P(X_i=x_i \cap X_i+X_j=t)}{P(X_i+X_j=t)} \\ &= \frac{\frac{n!}{x_i!(t-x_i)!(n-t)!}p_i^{x_i}p_j^{t-x_i}\left(1-p_i-p_j\right)^{n-t}}{\frac{n!}{t!(n-t)!}(p_i+p_j)^t(1-p_i-p_j)^{n-t}} \\ &= \frac{t!}{x_i!(t-x_i)!}\left(\frac{p_i}{p_i+p_j}\right)^{x_i}\left(\frac{p_j}{p_i+p_j}\right)^{t-x_i} \end{align*} So the conditional distribution of $X_i$, given $X_i+X_j=t$, is binomial with parameters $t$ and $\frac{p_i}{p_i+p_j}$, as claimed.


You have a series of trials which may be of result $I$ or $J$ with mutually exclusive probabilities of $p_i$ or $p_j$.

You are given the condition that exactly $t$ trials are either type $I$ or $J$.

The conditional probability that any one of these events is type $I$ given that it is either type $I$ or type $J$ will be: $\dfrac{p_i}{p_i+p_j}$ (you can see why?)

So the count of events of type $I$ among when given this condition will have a binomial distribution, because we have a series of Bernoulli trials.

Thus you obtain: $$X_i \mid X_i+X_j \;\sim \; \mathcal{Bin}(t, \dfrac{p_i}{p_i+p_j})$$

$$\mathsf P(X_i\mid X_i+X_j = t) = \dbinom{t}{x_i} \left(\dfrac{p_i}{p_i+p_j}\right)^{x_i} \left(1- \dfrac{p_i}{p_i+p_j}\right)^{t-x_i}$$

Alternatively we can condition the multinomial, by noting that the numerator is a multinomial distribution and the denominator is a binomial.

$$\begin{align} \mathsf P(X_i=x_i \mid X_i+X_j=t) &= \frac{\mathsf P(X_i=x_i, X_j=t-x_i)}{\mathsf P(X_i+X_j=t)} \\[2ex] &= \frac{\dbinom{N}{x_i, t-x_i, N-t} p_i^{x_i} p_j^{t-x_i}(1-p_i-p_j)^{N-t}}{\dbinom{N}{t, N-t} (p_i+p_j)^t (1-p_i-p_j)^{N-t}} \end{align}$$

Simplify this by cancelling terms and obtain the same answer.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.